Learning Solar System using Augmented Reality (AR) for Upper Primary School Kids - Ooi, Li Ying (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Augmented reality (AR) is the future of the education industry. It can motivate and engage students in the learning process. Currently, most of the primary school lack of hands-on learning. Therefore, this project proposed a mobile app to provide students to learn the solar system using AR. In this report, improvement and development are discussed to provide a better solution in learning. The proposed application testing will be including pre-test and posttest, and interview The purpose of testing is to evaluate the application is working fine and provide effective learning towards users. It is expected that the proposed application will provide effective learning modules into the mobile app.